2010
DOI: 10.2164/jandrol.109.007542
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α and β Polymorphisms Are Associated With Semen Quality

Abstract: The role of estrogen receptor a (ERa) and estrogen receptor b (ERb) gene polymorphisms on semen quality is the aim of our study. One hundred fourteen men were examined in the In Vitro Fertilization Unit of Ioannina Medical School, and it was found that 85 men had normal sperm count and 29 were oligozoospermic. The genotype analysis, on DNA extracted from spermatozoa, revealed that in men with oligozoospermia (sperm concentration ,20 6 10 6 spermatozoa/mL), those with ERa 397T/C and 397C/C genotypes had higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 48 publications
(67 reference statements)
0
43
2
Order By: Relevance
“…Spermatogenesis and sperm motility regulation are complicated processes in which the activity of aromatase and ERs cooperate, influencing testicular oestrogen levels. 44 Although the small number of subjects enrolled in this study may limit the impact of our findings, our results are nevertheless indicative of the significance of the CYP19 (TTTA) n polymorphism in semen quality. This study has shown, for the first time, an association between a cytochrome P450 aromatase gene polymorphism with sperm concentration and motility.…”
mentioning
confidence: 69%
“…Spermatogenesis and sperm motility regulation are complicated processes in which the activity of aromatase and ERs cooperate, influencing testicular oestrogen levels. 44 Although the small number of subjects enrolled in this study may limit the impact of our findings, our results are nevertheless indicative of the significance of the CYP19 (TTTA) n polymorphism in semen quality. This study has shown, for the first time, an association between a cytochrome P450 aromatase gene polymorphism with sperm concentration and motility.…”
mentioning
confidence: 69%
“…Polymorphisms in ER-␣ gene (XbaI and Pvull) have been shown to be associated with azoospermia or severe oligozoospermia [18,19]. In a study by Lazaros et al [25] in men with oligozoospermia those with ER-␣ 397T/C and 397C/C genotypes had higher sperm motility while those with 397T/T genotype had lower sperm motility. Overall, studies regarding regarding the effect of ER genes on male fertility have produced conflicting evidence [26,27].…”
Section: Introductionmentioning
confidence: 98%
“…Association between male infertility and polymorphisms in ER-␣ [18][19][20][21][22] and ER-␤ genes [23][24][25] has been shown in few studies. Polymorphisms in ER-␣ gene (XbaI and Pvull) have been shown to be associated with azoospermia or severe oligozoospermia [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The association between male infertility and ERα and ERβ gene polymorphisms has been explored in several studies that have produced conflicting results (Kukuvitis et al, 2002;Suzuki et al, 2002;Aschim et al, 2005;Lazaros et al, 2010). For example, PvuII and XbaI in ERα have been associated with azoospermia or severe oligozoospermia in 2 reports (Kukuvitis et al, 2002;Suzuki et al, 2002), but others have drawn different conclusions (Tuttelmann et al, 2007;Lazaros et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PvuII and XbaI in ERα have been associated with azoospermia or severe oligozoospermia in 2 reports (Kukuvitis et al, 2002;Suzuki et al, 2002), but others have drawn different conclusions (Tuttelmann et al, 2007;Lazaros et al, 2010). Moreover, RsaI and AluI in ERβ have been associated with male infertility in 2 studies (Aschim et al, 2005;Safarinejad et al, 2010), but the results could not be replicated (Khattri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%